Quality Analysis of Public Services for AK-1 Application at Disnakertrans Banten Province with Fuzzy Servqual - Finira, Dwinita Chika; Kusumah, Lien Herliani (AIBPM Publisher, 2023)
The Manpower and Transmigration Office, also known as Disnakertrans provides direct services to the community, including the issuance of the AK-I cover letter commonly known as the